RHETORICAL ANALYSIS OF CONTESTANT’S SPEECHES IN SPEECH CONTEST OF "STEC FESTIVAL BAHASA" COMPETITION AT IAIN KUDUS - Alfu Nikmah (International Journal of Research on English Teaching and Applied Linguistics, 2022)
Conducting speech contest in the college belongs to learning process in developing language skill. It is a kind of public speaking as realization of communicative competence in teaching and learning process. It conveys the message delivered to the audience. Message must be prepared in written form before it is performed . then the teacher must guide the students in constructing the text in delivering the message. Speech was performed has to fulfill the structure of organization and supplementary components. One of the strategic in delivering good speech is rethorical language. Rethorical languge consist of suppoting language developed in the speech for example hyperbole, alliteration, metaphor, repetition, irony, metonymies and rethorical question. This study conducted the the reseach to determine the importance speech in the teaching and learning proses. This study analysed the structure of the text. Moreover this study also revealed the rethorical language of the winner of speech competition held in IAIN Kudus. It was conducted using descriptive qualitative method in which the data anlysis used content anaysis. Based the analysis ,It was found that there were 9 items of rethorical language from the speech text that consist of 5 metaphors and 4 rethorical questions.